Market Value Ratio Analysis of Stock Returns In Companies With Largest Market Capitalization Period 2014-2018 - Ardi Tri Pangestu; Ade Suryana (Neraca : Jurnal Akuntansi Terapan, 2020)
This research aims to analyze how much influence the Market Value Ratio has on Stock Returns (case studies are conducted against companies with the largest market capitalization listed on the Indonesia Stock Exchange). The variables used in the analysis in this study are using Price Earning Ratio, Earning Yield, Dividend Yield, and Market to Book Ratio.The samples selected in this study used purposive sampling methods with a total of 13 stocks and produced 50 sample ratios studied according to the criteria and qualified in the year specified in 2014-2018. The method of analysis used in this study is to use statistical methods of descriptive analysis and linear regression multiplely by using SPSS software.Based on the results of the hypothesis, it is known that the Price Earning Ratio has a significant influence on the return of the stock, The Earning Yield has an effect but is not significant on the return of the stock, the Dividend Yield and the Market to Book Ratio have no effect on the return of the stock, and the Market Value Ratio simultaneously (together) affects the return of the stock.